2006
DOI: 10.1080/00221686.2006.9521701
|View full text |Cite
|
Sign up to set email alerts
|

Scour holes downstream of bed sills in low-gradient channels

Abstract: An experimental study on long local scouring downstream of bed sills in a monogranular sand bed was carried out in the hydraulic laboratory flume at the Mediterranean Agronomic Institute of Bari (Italy). The main objectives of this study were to determine scour hole dimension, with its maximum scour depth as a function of time and at the equilibrium stage, the scour hole shapes and the investigation of the influence of sills on the distribution of the three-velocity components through the scour hole at the sam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
59
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(70 citation statements)
references
References 13 publications
4
59
0
Order By: Relevance
“…Scour length needs to be estimated for protecting river embankments to avoid excessive bank erosion. Prediction formulae calibrated on experimental and field data for both scour depth and length are available to designers [ Gaudio et al , 2000; Lenzi et al , 2003a; Marion et al , 2004; Meftah and Mossa , 2006; Martín‐Vide and Andreatta , 2006]. In this paper the geometric properties of the scour profile are analytically discussed and verified on the basis of experimental data from literature.…”
Section: Introductionmentioning
confidence: 99%
“…Scour length needs to be estimated for protecting river embankments to avoid excessive bank erosion. Prediction formulae calibrated on experimental and field data for both scour depth and length are available to designers [ Gaudio et al , 2000; Lenzi et al , 2003a; Marion et al , 2004; Meftah and Mossa , 2006; Martín‐Vide and Andreatta , 2006]. In this paper the geometric properties of the scour profile are analytically discussed and verified on the basis of experimental data from literature.…”
Section: Introductionmentioning
confidence: 99%
“…They concluded that this structure typology can be successfully adopted to prevent erosion in incised channels and furnished equation to satisfactorily assess scour-hole characteristics downstream of them. A similar analysis was conducted by Ben Meftah and Mossa (2006), who studied the erosive processes due to bed sills. In addition, Bhuiyan et al (2007) studied the scour development downstream of W-weirs.…”
Section: Introductionmentioning
confidence: 77%
“…Some studies have investigated the stochastics nature of turbulent flow around a pier [2,[7][8][9][10][11], but there still remains a lack information concerning the trend of higher order moments for the fluctuating velocities.…”
Section: Introductionmentioning
confidence: 99%